Effectiveness of exchange rate in Pakistan: Causality analysis - Rana Ejaz Ali Khan; Rashid Sattar; Hafeez Ur Rehman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
The study analyzed the effectiveness of exchange rate on macroeconomic variables of Pakistan. The precise objective of the study is to examine the causality between exchange rate, trade, inflation, FDI and GDP through a series of models. On the annual time series data for the years 1980-2009 unit root test for stationarity, Johansen's cointegration test for long-run equilibrium relationship between the variables for each model and Granger Causality test to check the causality between the variables is applied. The main findings are as: there is no long-run equilibrium relationship between exchange rate and inflation, but there exists long-run equilibrium relationship between exchange rate and trade. There is also long-run equilibrium relationship between exchange rate and FDI and causality runs in both directions, i.e. exchange rate to FDI and FDI to exchange rate. Finally, there is long-run equilibrium relationship between exchange rate and GDP but causality does not run in either direction.
Keywords: 330; Exchange rate; Pakistan; Inflation; FDI; GDP; Wechselkurs; Inflation; Auslandsinvestition; Nationaleinkommen; Pakistan